Beyond tipping points: risks, equity, and the ethics of intervention - L. M. Pereira; L. M. Pereira; S. R. Smith; S. R. Smith; L. Gifford; P. Newell; S. Villasante; T. Achieng; A. Castro; A. Castro; S. M. Constantino; T. Powell; et al. (Earth System Dynamics)
Earth system tipping points pose existential threats to current and future generations, both human and non-human, with those least responsible for causing them facing the greatest risks. “Positive” social tipping points (that we shorten to positive tipping points, or PTPs) are often deliberate interventions into social systems with the aim of rapidly mitigating the risks of Earth system tipping. However, the desire to intervene should neither increase risks nor perpetuate unjust or inequitable outcomes through the creation of sacrifice zones. In this paper, we argue that considerations of what needs to change, who is being asked to change, and where and by whom the impacts of change will be felt are fundamental and normative questions that require reflexivity and systemic understanding of decision-making across scales. All actors have a role to play in ensuring that justice, equity, and ethics are carefully considered before any intervention. Enabling positive tipping points for radical transformations would thus benefit from more diverse perspectives, with a particular emphasis on the inclusion of marginalized voices in offering solutions. We conclude that taking a cautious approach to positive tipping interventions, including careful consideration of distributional and unintended consequences, and stepping back to explore all options, not just those appearing to offer a quick fix, could lead to more equitable and sustainable outcomes.